2018
DOI: 10.1155/2018/8701890
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Diffusion Bonding between Titanium Alloys and Stainless Steels

Abstract: High-quality joints between titanium alloys and stainless steels have found applications for nuclear, petrochemical, cryogenic, and aerospace industries due to their relatively low cost, lightweight, high corrosion resistance, and appreciable mechanical properties.is article reviews diffusion bonding between titanium alloys and stainless steels with or without interlayers. For diffusion bonding of a titanium alloy and a stainless steel without an interlayer, the optimized temperature is in the range of 800-950… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 90 publications
1
37
0
1
Order By: Relevance
“…A summary of the growth kinetics of the reaction layer is shown in Table 3. The activation energy was calculated to be 111.4 kJ/mol for a bonding temperature of 850 • C. This is similar to findings published in the scientific literature which suggest that the activation energy for the formation of Ti 2 Cu is approximately 122.1 kJ/mol [16]. In this study, the calculation of the activation energy was performed based on a simplified diffusion model, which assumes diffusion in a single phase which is influenced by the thickness of the reaction layer formed during the diffusion bonding process and the increases in the rate coefficient.…”
Section: Growth Kinetics Of Interfacial Phasessupporting
confidence: 86%
See 1 more Smart Citation
“…A summary of the growth kinetics of the reaction layer is shown in Table 3. The activation energy was calculated to be 111.4 kJ/mol for a bonding temperature of 850 • C. This is similar to findings published in the scientific literature which suggest that the activation energy for the formation of Ti 2 Cu is approximately 122.1 kJ/mol [16]. In this study, the calculation of the activation energy was performed based on a simplified diffusion model, which assumes diffusion in a single phase which is influenced by the thickness of the reaction layer formed during the diffusion bonding process and the increases in the rate coefficient.…”
Section: Growth Kinetics Of Interfacial Phasessupporting
confidence: 86%
“…While interdiffusion led to the formation of a wide region, labelled A, the nanoparticles appear to have segregated to form a thick layer at the SDSS interface. EDS analysis of the dark grey particles showed that the Al 2 O 3 particles reacted with Cu and Fe [15,16]. observed at the interface on the Ti side of the bond.…”
Section: Effect Of Bonding Time On the Bond Interfacementioning
confidence: 99%
“…From Fig. 4, it is found that the room temperature (RT) tensile properties (both LSS and BS) of the DB joints increases constantly during the time break from 45 to 90 min and drops at 105 min [8,9], for a bonding temperature of 925 °C and bonding pressure of 14 MPa. With the increase of holding time from 45 to 90 min, the blending of mating surfaces enhances the room temperature properties of the DB joints, and additionally, offer some beneficial effect.…”
Section: Tensile Propertiesmentioning
confidence: 98%
“…e layer metal laminated materials were made of two or more single-layer metals by suitable composite technology [7][8][9]. It combined the advantages of single-component metal, which not only made the application value of single metal fully play but also can reduce the amount of precious metal, improve the deficiency of single metal, and better adapt to the industrialization and market-oriented development [10][11][12]. Titanium and aluminum alloys can be made into layered Ti-Al laminated plates by laminated technology.…”
Section: Introductionmentioning
confidence: 99%